The sustained inward current and inward rectifier K(+) current in pacemaker cells dissociated from rat sinoatrial node - Shinagawa, Yasuko (Blackwell Science Inc, 2000)
1. Myocytes were dissociated from the sinoatrial (SA) node of rat heart using a new enzymatic dissociation technique. Only a small number of isolated SA node myocytes showed regular rhythmic contractions and spontaneous action potentials, and these were used in the present study. 2. The spontaneous action potential was resistant to TTX, and the action potential parameters were similar to those of rabbit and guinea-pig pacemaker cells. Major time- and voltage-dependent currents were the delayed rectifier K(+) current I(Kr), the L-type Ca(2+) current I(Ca,L) and the sodium current I(Na). The hyperpolarization-activated cation current (I(f)) was recorded from ≈50 % of the cells with hyperpolarization beyond -90 mV. 3. The instantaneous current jump at the onset of a hyperpolarizing pulse showed inward rectification and was largely blocked by Ba(2+). This Ba(2+)-sensitive current corresponded well to the inward rectifier K(+) current (I(K1)), although it was much smaller in amplitude than in the ventricle. 4. A sustained inward current was activated on depolarization from -80 mV to the voltage range of slow diastolic depolarization. The current was blocked by nicardipine, enlarged by isoprenaline and was insensitive to removal of external Ca(2+). These characteristics were similar to the sustained inward current, I(st), previously described in the rabbit and guinea-pig SA node cells. 5. The role of I(st) was considered by constructing empirical equations, which were applied to the experimental record of the action potential. It is demonstrated that the voltage-dependent activation of I(st) constitutes a positive feedback loop with the depolarization of the membrane.